DeepBlack - Waleed T. Saleh; Mohammad Al-Bzoor (My University, 2023)
Bringing chess to the physical world, defeating loneliness, and helping players train and be mentally prepared to play on an actual board rather than a mobile app or website are the pillars of this project. Features the application includes : • the ability to move the pieces. • Provide a built-in timer with a button to indicate the turns. • A warning indication in case an illegal move occurred. • A sign to show the end of the game. • Provide a way to let the robot automatically detect the moves.
DeepBlack